The one hundredth day of school! - Klein, Abby; McKinley, John (New York : Blue Sky Press, 2008)
Freddy decides to bake one-hundred cookies for the one hundredth day of school celebration, but his father accidently eats one and then Freddy has to come up with another idea at the last minute.
Keywords: Families -- Juvenile fiction; Fiction